The safety performance of guardrail systems: review and analysis of crash tests data - Soltani, M.; Moghaddam, T.B.; Karim, M.R.; Sulong, N.H.R. (2013)
The last decade has witnessed an increased number of vehicles and increased vehicle speed on roads such that the frequency and severity of run-off roadway accidents has increased dramatically. Evaluation of guardrail system performance as an element of providing a safe environment for vehicles and to reduce occupant injuries is deemed to be vital issue. Hence, this paper is going to assess deflection and vehicle trajectory of current guardrail systems. For this purpose, the results of full-scale crash tests for different types of guardrail system are collected from previous crash tests available in the literature. The results showed that for Test 3-11 (according to NCHRP Report 350) with similar post spacing (1905 mm), the trend of vehicle exit speed declined while guardrail maximum permanent deflection increased. In addition, among all system types, guardrail with curb and Thrie-beam guardrail systems were subjected to the lowest amount of deflection although Thrie-beam guardrail was subjected to higher average values for both vehicle exit speed and exit angle. Further, weak-post guardrail system showed to have the highest maximum dynamic and permanent deformation compared to other systems whereas it caused the lowest exit angle to the vehicles.